Pengenalan Nilai-nilai Kebaikan melalui Manajemen Program Asmaul Husna Berbasis Gerak dan Lagu - Wahyuningsih Wahyuningsih; Novan Ardy Wiyani (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
The purpose of this study is to describe and analyze the introduction of values of goodness through the management of a movement- and song-based Asmaul Husna program at RA Bani Malik Ledug. This research employed a qualitative approach. Data were collected through observation, interviews, and documentation, and then analyzed using data analysis techniques consisting of data reduction, data display, and verification. The results show that the planning stage of the movement- and song-based Asmaul Husna program was designed so that within one week, children memorize three names of Allah until completing all 99 names. The organizing stage involved the principal conveying the established plan to teachers and parents, including the number of Asmaul Husna to be memorized by children each week. The implementation stage indicates that the program is conducted daily before formal learning activities begin, specifically during the time allocated for Islamic learning. In the controlling stage, the principal evaluates the implementation outcomes of the program and identifies both inhibiting and supporting factors influencing its execution.